Consciousness, Matter, Brain Neural Activity and Telepathy - Segman, Yosef Joseph (European Journal of Applied Sciences, 2024)
The purpose of this paper is to mathematically define cords of consciousness (CoC) and consciousness by the act of brain neural patterns, wherein neutral patterns represent synchronized groups of neurons. The outcome of neural patterns represents cords of consciousness. Conversely, the cords of consciousness exhibit neural patterns. Cords of consciousness represent the space of information embedded within the one unique timeless and dimensionless metaphysical space. This paper elaborates on the physical and metaphysical relationships between physical brain neural activity and consciousness metaphysical sensation. For example, dreams, lucid dreams, ideas, memories, and out-of-body sensations (OBE or Astral Projection) are consciousness metaphysical sensations resulting in physical brain neural activity. Individual consciousness is defined as the collection of the individual’s cords of consciousness. Furthermore, consciousness is a virtual junction on the metaphysical consciousness virtual net where each junction incorporates a set of cords of consciousness. The set can be limited, unlimited or unaccountable. Cords of consciousness can be learned from the brain’s neural patterns, and thus, memories can be manipulated by installing external neural patterns that create sensations of artificial consciousness.